2018
DOI: 10.1136/sextrans-2017-053491
|View full text |Cite
|
Sign up to set email alerts
|

Will an innovative connected AideSmart! app-based multiplex, point-of-care screening strategy for HIV and related coinfections affect timely quality antenatal screening of rural Indian women? Results from a cross-sectional study in India

Abstract: ObjectivesIn rural pregnant Indian women, multiple missed antenatal screening opportunities due to inadequate public health facility-based screening result in undiagnosed HIV and sexually transmitted bloodborne infections (STBBIs) and conditions (anaemia). Untreated infections complicate pregnancy management, precipitate adverse outcomes and risk mother-to-child transmission. Additionally, a shortage of trained doctors, rural women’s preference for home delivery and health illiteracy affect health service deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Our study population represents adult population who are at increased risk of HBV (key population) in the state of Tamil Nadu, South India. The key population considered in the study includes individuals with sexual risk behaviours [9], individuals with STDs [10], people living with HIV [11,12], blood donors [13,14,15], antenatal women [16,17] and men who have sex with men (MSM) [18].…”
Section: Methodsmentioning
confidence: 99%
“…Our study population represents adult population who are at increased risk of HBV (key population) in the state of Tamil Nadu, South India. The key population considered in the study includes individuals with sexual risk behaviours [9], individuals with STDs [10], people living with HIV [11,12], blood donors [13,14,15], antenatal women [16,17] and men who have sex with men (MSM) [18].…”
Section: Methodsmentioning
confidence: 99%
“…Testee preference for multiplexed testing varied from a low of 60.2% to a high of 97.2% among study participants. 18 19 21 Overall, participants reported high satisfaction with being tested by multiplexed technologies (92.0%-99.5%) 19 21 and high acceptance of multiplexed technologies (100.0%). 18 21 With regard to recommendation, up to 99.1% of study participants would recommend multiplexed technologies to others.…”
Section: Preference and Feasibilitymentioning
confidence: 99%
“…The impact of multiplexed technologies was defined in one of several ways including their ability to detect new infections, increase uptake and to improve turnaround times to test results and linkages to care. Impact was reported by 11 (25.6%) where 3 (6.8%) studies reported on the increased detection of new/previously undiagnosed infections as a result of multiplexed testing, 1 (2.3%) study reported the increase in multiplexed testing from baseline, 21 6 (13.9%) studies reported the turnaround time to test results, [22][23][24][25][26][27] and 3 (6.9%) reported on linkages to/retention in care 18 21 28 (table 1).…”
Section: Impactmentioning
confidence: 99%
See 2 more Smart Citations